Student’s Response to Mathematics Learning in Probability Materials - Febriyandi Nurhidayat; Usman Aripin (IKIP Siliwangi, 2023)
Most people, especially the subjects that are very disliked learning mathematics because mathematics is famous for being difficult and boring. This happens because especially the demonstration techniques used by educators cannot benefit and influence the understanding of science. This study uses an approach to finding a substitute model for learning mathematics on the subject of probability. The procedure in this research is divided into three stages, namely: (1) the preparation phase (2) the implementation phase (3) and the opening phase. This study aims to determine students' reactions to learning mathematics on the subject of probability. In addition, respondents completed a poll of 10 questions with 4 possible answers, specifically SS (Strongly Agree), S (Agree), TS (Disagree), and STS (Strongly Disagree). From the results of this study, it can be said that the student's response to learning mathematics in the subject of opportunity received a strong and positive response. Opinion questionnaires can be developed more deeply and supplemented by additional meetings thoroughly.